A stabilized retro-inverso peptide ligand of transferrin receptor for enhanced liposome-based hepatocellular carcinoma-targeted drug delivery. (1st January 2019) - Tang, Jiajing; Wang, Qiantao; Yu, Qianwen; Qiu, Yue; Mei, Ling; Wan, Dandan; Wang, Xuhui; Li, Man; He, Qin
Graphical abstract: Abstract: The application of tumor targeting ligands to the treatment of cancer holds promise for improving efficacy and reducing toxicity. L T7 (L (HAIYPRH)) peptide, a phage display-selected peptide, exhibited high binding affinity to transferrin receptor (TfR) overexpressed on tumor cells. However, its in vivo tumor targeting efficiency was impaired due to enzymatic degradation in blood circulation. To improve the stability and targeting ability, a retro-inverso analogue of L T7 peptide, named D T7 peptide (D (HRPYIAH)), was designed for targeted therapy of hepatocellular carcinoma. The result of computer simulation predicted that D T7 bound to TfR protein more efficiently than L T7, and this prediction was confirmed experimentally by surface plasmon resonance (SPR). Ex vivo stability experiment demonstrated that D T7 possessed stronger ability against proteolysis than L T7 in fresh mouse serum. We further prepared D T7-, L T7-, and transferrin (Tf)-modified liposomes ( D T7-LIP, L T7-LIP, and Tf-LIP, respectively). D T7-LIP showed a significantly stronger in vitro targeting ability than L T7-LIP and Tf-LIP under normal condition and simulated biological condition. In addition, the in vitro antitumor effect of DTX-loaded D T7-LIP was markedly enhanced in comparison to DTX-loaded L T7-LIP and DTX-loaded Tf-LIP. In vivo imaging indicated that D T7-LIP had better tumor accumulation than L T7-LIP and Tf-LIP. For in vivo antitumor studies, the tumor growth rate of mice treated with DTX-loaded D T7-LIP was significantly inhibited compared to that in mice treated with DTX-loaded L T7-LIP and DTX-loaded Tf-LIP. Overall, this study verified the potential of the stable D T7 peptide in improving the efficacy of docetaxel in the treatment of hepatocellular carcinoma. Statement of Significance: A phage display library-selected L T7 (L (HAIYPRH)) peptide exhibited high affinity to transferrin receptor (TfR). However, its bioactivity was impaired in vivo as L-peptides are susceptible to degradation by proteolytic enzymes. Here, we designed a retro-inverso peptide D T7(D (HRPYIAH)) and demonstrated its increased serum stability and higher binding affinity to TfR. A stabilized targeted drug delivery system was further constructed by modified D T7 peptide on the surface of liposomes. The data indicated that D T7 peptide-modified liposomes exhibited higher targeting ability in vitro and in vivo . More importantly, D T7-modified liposomes demonstrated positive preclinical significance in enhancing the therapeutic effects against hepatocellular carcinoma.